Mutation of DEFECTIVE EMBRYO SAC1 results in a low seed-setting rate in rice by regulating embryo sac development. (18th January 2023) - Hu, Xia; Yu, Ping; Zhang, Yingxin; Gao, Zhiqiang; Sun, Bin; Wu, Weixun; Deng, Chenwei; Abbas, Adil; Hong, Yongbo; Sun, Lianping; Liu, Qunen; Xue, Pao; et al.
Abstract: The seed-setting rate has a significant effect on grain yield in rice ( Oryza sativa L.). Embryo sac development is essential for seed setting; however, the molecular mechanism underlying this process remains unclear. Here, we isolated defective embryo sac1 ( des1 ), a rice mutant with a low seed-setting rate. Cytological examination showed degenerated embryo sacs and reduced fertilization capacity in des1 . Map-based cloning revealed a nonsense mutation in OsDES1, a gene that encodes a putative nuclear envelope membrane protein (NEMP)-domain-containing protein that is preferentially expressed in pistils. The OsDES1 mutation disrupts the normal formation of functional megaspores, which ultimately results in a degenerated embryo sac in des1 . Reciprocal crosses showed that fertilization is abnormal and that the female reproductive organ is defective in des1 . OsDES1 interacts with LONELY GUY (LOG), a cytokinin-activating enzyme that acts in the final step of cytokinin synthesis; mutation of LOG led to defective female reproductive organ development. These results demonstrate that OsDES1 functions in determining the rice seed-setting rate by regulating embryo sac development and fertilization. Our study sheds light on the function of NEMP-type proteins in rice reproductive development. Abstract : OsDES1 encodes a NEMP-domain protein that interacts with a cytokinin-activating enzyme, LOG, to determine the seed-setting rate in rice by regulating embryo sac development.